“Plan estratégico para desarrollar ventajas competitivas en la carrera de Administración de Empresas de la Universidad Técnica de Cotopaxi extensión La Maná en el periodo 2022”. - Oña Almache, Yesenia Maribel (2022)
The achievement of the objectives is vital for the permanence in time and growth, therefore the application of strategies represents the roadmap that must be applied to achieve success. The problem arose with the need to broaden the vision and raise awareness about the strategic plan to develop competitive advantages within the current legal framework. The following research had as its objective: "Design the strategic plan that allows the development of competitive advantages for the institutional strengthening of the Business Administration major of the Universidad Técnica de Cotopaxi extensión La Maná period 2022- 2024", in order to fulfill this purpose we proceeded to conduct a bibliographic and field research, to determine the results obtained the research was based on a qualitative approach, descriptive, documentary - bibliographic, field research was used, compiling information from primary and secondary sources, using techniques and instruments of observation, survey, and checklist. The most relevant results indicated that there is no anticipatory and prospective management since techniques are not used to foresee a future situation, policies on alternative scenarios are not defined and matrices of opportunities and threats are not analyzed. Therefore, it is concluded that the strategic plan will allow the improvement and perception of the major. In view of the results found, recommendations were made that can be implemented to improve the aforementioned problems.